(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of the current study was to evaluate the activity of Shikimic acid (SA) and Acetylsalicylic acid (ASA) against S. epidermidis biofilms formation in different conditions. A total of (231) samples were collected from patients who attended different hospitals in Ramadi and Faluja cities during the period from December(2020) to the end of July (2021). Samples were cultured on blood, and manitol salt agar and identification was performed by the VITEK 2 system. Antibiofilm activity of SA was evaluated by two methods, modified crystal violet, and MTT assay. The SA was tested in five MIC (0.25 MIC, 0.5 MIC, MIC2, MIC, and 4 MIC) and was tested during different incubation periods (2 hr, 4 hr, 6 hr, 12 hr, and 24 hr), Shikimic acid gave highest percentage inhibition of biofilm formation was 93% at 12hr and ,94% at 24hr , while Acetyl salicylic acid was gave 85% at 12hr and 91% at 24hr incubation period . Then evaluated the synergistic activity of SA and ASA acid with ceftriaxone and azithromycin against biofilm formation also then determination of the antibiofilm activity of SA and ASA acid against bacteria adherence to Foley balloon latex catheter (FBLC) pieces by REMA assay.In addition, determine the efficacy of SA and ASA acid against cell adherence using murine mammary adenocarcinoma cell line (amn3)cells. The results showed high percentage inhibition of biofilm formation as the concentration of SA and ASA increased . In conclusion, SA and ASA have the potential to be further developed as a new antitumor agent due to their impressive antibiofilm action against bacteria. shikimic acid , acetyle salicylic acid were gave up regulation of atlE gene , 2 ( −ΔΔCT) was (2)for shikimic acid while (3)for acetyl salicylic acid , aap,icaA genes, all antibiofilm agents were gave down regulation result 2 ( −ΔΔCT) was (0.2)for shikimic acid while (0.1)for acetyl salicylic acid.